Co-Creativity and Engaged Scholarship Transformative Methods in Social Sustainability Research - Franklin, Alex (Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This open access book explores creative and collaborative research methods within the social sustainability sciences. The term co-creativity is used in reference to both individual methods and overarching research approaches that, through socially inclusive forms of action and reflection, stimulate alternative understandings of why and how things are, and how they could be. Supported by a wide-ranging series of in-depth-including chapters on militant research and guerrilla narrative, decolonial participative approaches, appreciate inquiry and care-ethics, deep-mapping, photo-voice, community-arts, digital participatory mapping, and living labs-the edited collection critically reviews the potential of creative, collaborative and transdisciplinary forms of research praxis to nurture just and transformative processes of change. This includes considering the role of narrative, creative workshops, visual and arts-based forms of research in contributing to engaged scholarship, as well also as a range of methods from field of critical cartography. The positionality of the researcher, together with the emotional and embodied dimensions of 'doing' transdisciplinary research are threads which run throughout the collection. So too does the question of how to communicate sustainability science research in meaningful way.